Comprehensive care for people living with heart failure and chronic obstructive pulmonary disease—Integration of palliative care with disease-specific care: From guidelines to practice - Kowalczys, Anna; Bohdan, Michał; Wilkowska, Alina; Pawłowska, Iga; Pawłowski, Leszek; Janowiak, Piotr; Jassem, Ewa; Lelonek, Małgorzata; Gruchała, Marcin; Sobański, Piotr (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) and chronic obstructive pulmonary disease (COPD) are the leading global epidemiological, clinical, social, and economic burden. Due to similar risk factors and overlapping pathophysiological pathways, the coexistence of these two diseases is common. People with severe COPD and advanced chronic HF (CHF) develop similar symptoms that aggravate if evoking mechanisms overlap. The coexistence of COPD and CHF limits the quality of life (QoL) and worsens symptom burden and mortality, more than if only one of them is present. Both conditions progress despite optimal, guidelines directed treatment, frequently exacerbate, and have a similar or worse prognosis in comparison with many malignant diseases. Palliative care (PC) is effective in QoL improvement of people with CHF and COPD and may be a valuable addition to standard treatment. The current guidelines for the management of HF and COPD emphasize the importance of early integration of PC parallel to disease-modifying therapies in people with advanced forms of both conditions. The number of patients with HF and COPD requiring PC is high and will grow in future decades necessitating further attention to research and knowledge translation in this field of practice. Care pathways for people living with concomitant HF and COPD have not been published so far. It can be hypothesized that overlapping of symptoms and similarity in disease trajectories allow to draw a model of care which will address symptoms and problems caused by either condition.